2014
DOI: 10.1108/cdi-01-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Examining the interactive effects of accountability, politics, and voice

Abstract: Purpose – Research has shown accountability can produce both positive and negative outcomes. Further, because of inherent environmental uncertainty, perceptions of organizational politics often interact with accountability to produce negative effects. However, using uncertainty management theory, the purpose of this paper is to argue that employees can use proactive voice to exercise control in the ambiguity of highly accountable and political environments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 83 publications
0
17
0
1
Order By: Relevance
“…Further, we found only one study that examined this relationship in organizational contexts. Hochwarter, Ellen, and Ferris () found that proactive voice ameliorated deleterious outcomes (such as job tension) when individuals felt highly accountable and had high perceptions of workplace politics. Just as with conflict, the implications of voice on accountability warrant further investigation.…”
Section: Empirical and Methodological Issues In Accountability Researchmentioning
confidence: 99%
“…Further, we found only one study that examined this relationship in organizational contexts. Hochwarter, Ellen, and Ferris () found that proactive voice ameliorated deleterious outcomes (such as job tension) when individuals felt highly accountable and had high perceptions of workplace politics. Just as with conflict, the implications of voice on accountability warrant further investigation.…”
Section: Empirical and Methodological Issues In Accountability Researchmentioning
confidence: 99%
“…Therefore, accountability perceptions are usually subjective depending upon personal standards rather than organizational norms or universal values [83]. Accountability is deemed essential for effective management of any organization [84].…”
Section: Raised Need For Accountabilitymentioning
confidence: 99%
“…Accountability, by no means is an agent for control to be used by supervisors to discipline workers [85]; it is needed more for managers and supervisors to know how they are supervising? Supervising does not mean policing around and it is observed when people are left to their personal discretion, some of them tend to use power according to their own understanding, using it to gain personal interests rather than focusing on larger good [83].…”
Section: Raised Need For Accountabilitymentioning
confidence: 99%
“…For example, politics perceptions were related to positive outcomes when employees were aware of gamesmanship at work (Ferris, Russ, & Fandt, 1989). Heightened politics were viewed as favorable when accountability and voice were high (Hochwarter, Ellen, & Ferris, 2014). Yen (2015) reported that salespersons reporting high levels of politics perceptions were the highest performers as well as the most intrinsically motivated.…”
Section: Literature Reviewmentioning
confidence: 99%